Food insecurity, state fragility and youth mental health: A global perspective - Frank J. Elgar; Akankasha Sen; Geneviève Gariépy; William Pickett; Colleen Davison; Kathy Georgiades; Nour Hammami; Marine Azevedo Da Silva; David Gordon; Hugo Ramiro Melgar-Quiñonez (Elsevier, 2021)
Youth in fragile settings face disproportionate risks of experiencing food insecurity and poor mental health. Cross-national evidence is lacking on the association between food insecurity and mental health in youth populations, and on state fragility as a social determinant of these experiences. We analysed data from six cycles of the Gallup World Poll (2014-2019), an annual survey that contains multi-item scales of food insecurity, mental health problems and positive wellbeing. The analytic sample included 164,118 youth aged 15-24 years in 160 states. We linked individual responses to state-level data from the Fragile States Index-an aggregate measure of state vulnerability to collapse or conflict (coded: sustainable, stable, warning, or alert) and estimated adjusted relative risk (RR) of food insecurity as a function of state fragility. We then used linear regression to examine associations of state fragility and food insecurity with mental health and wellbeing. The prevalence of moderate or severe food insecurity rose from 22.93% in 2014 to 37.34% in 2019. State fragility (alert vs. sustainable) was related to an increased risk of food insecurity (RR = 2.28 [95% CI 1.30 to 4.01]), more mental health symptoms (b = 6.36 [95% CI 1.79 to 10.93]), and lower wellbeing (b = −4.49 [95% CI -8.28 to −0.70]) after controlling for state wealth and household income. Increased food insecurity (severe vs. none or mild) was uniquely related to more mental health symptoms (b = 18.44 [95% CI 17.24 to 19.64]) and reduced wellbeing (b = −9.85 [95% CI -10.88 to −8.83]) after state fragility was also controlled. Globally, youth experience better mental health where states are more robust and food access is more secure. The findings underscore the importance of strong governance and coordinated policy actions that may improve youth mental health.